2013
DOI: 10.1152/ajprenal.00560.2012
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid-induced phenotypic transition of renal tubular cells as a novel mechanism of chronic kidney disease

Abstract: Ryu ES, Kim MJ, Shin HS, Jang YH, Choi HS, Jo I, Johnson RJ, Kang DH. Uric acid-induced phenotypic transition of renal tubular cells as a novel mechanism of chronic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
183
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(193 citation statements)
references
References 58 publications
(90 reference statements)
6
183
0
4
Order By: Relevance
“…A primary role of UA on the renal tubules is further supported by the observation that phenotypic transition of the renal tubules in hyperuricemia occurred before the development of GFR reduction and that significant tubulointerstitial fibrosis could be ameliorated by lowering UA. 13 We showed that high UA level was independently associated with tubulointerstitial damage in patients with diverse causes of primary GN consistent with previous studies in IgA nephropathy. 27,28 Similar to other studies, we found that UA levels correlated inversely with GFR.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A primary role of UA on the renal tubules is further supported by the observation that phenotypic transition of the renal tubules in hyperuricemia occurred before the development of GFR reduction and that significant tubulointerstitial fibrosis could be ameliorated by lowering UA. 13 We showed that high UA level was independently associated with tubulointerstitial damage in patients with diverse causes of primary GN consistent with previous studies in IgA nephropathy. 27,28 Similar to other studies, we found that UA levels correlated inversely with GFR.…”
Section: Discussionsupporting
confidence: 91%
“…In experimental animals, hyperuricemia could induce endothelial dysfunction and vascular smooth muscle proliferation leading to secondary tubulointerstitial injury through reductions in GFR and ischemia. 4,10 Recent studies have also suggested that UA may act directly on renal tubules by stimulating cytokines production 26 and epithelial-to-mesenchymal transition, 13 which are key events in renal fibrosis. A primary role of UA on the renal tubules is further supported by the observation that phenotypic transition of the renal tubules in hyperuricemia occurred before the development of GFR reduction and that significant tubulointerstitial fibrosis could be ameliorated by lowering UA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include endothelial dysfunction, renal angiotensin system activation, oxidative stress, and tubular epithelial cell transition. [22][23][24][25][26] In addition, uric acid can also trigger vascular smooth muscle cell proliferation 27 and inflammation by activating transcription factor, such as NF-kB and inducing production of chemokines/chemokines-like TNF-a, IL-1b, monocyte chemoattractant protein-1 (MCP-1) and regulated on activation, normal T cell expressed and secreted (RANTES). 28,29 Numerous studies have shown that activation of the TGF-b signaling pathway contributes to glomerular sclerosis and tubulointerstitial fibrosis induced by various insults including hyperuricemia.…”
mentioning
confidence: 99%
“…З часом спостерігалися інтерстицій-не ураження і гломерулосклероз [10]. Гіперурикемія також індукувала епітеліально-мезенхімальну транс-формацію [18]. Особливо вираженими ефекти були у тварин із попередньо існуючим ураженням нирок, у яких гіперурикемія прискорювала розвиток клубоч-кової гіпертензії і судинних уражень, в результаті чого прогресувала протеїнурія і ниркова недостатність.…”
Section: Looking At the Problemunclassified